A Bibliometric and Trend Analysis on Fuzzy Risk Assessment - Cebi, Selcuk; Kahraman, Cengiz; Oztaysi, Basar; Onar, Sezi Cevik (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
Fuzzy risk assessment methods encompass a wide range of techniques used in various fields such as finance, engineering, and environmental science. The main objective of this study is to provide an overview on risk assessment methods used in the literature. An investigation was conducted to analyze research trends by examining the distribution of countries, journals, author keywords, and the used methods by integrating fuzzy sets. For the analysis, the data spanning from 1977 to 2024 were collected from the Scopus database. Between 2017 and 2022, there has been a significant rise in the number of scientific publications focusing on fuzzy risk assessment analysis. China has a significantly higher number of publications on fuzzy risk assessment compared to other countries. In the studies, different methods from many fields ranging from machine learning to statistical decision making have been used in integration with fuzzy logic. Analytic hierarchy process (AHP) exhibits a notably high usage count, followed by other commonly used methods Fuzzy Inference systems (FIS) and Failure modes and effects analysis (FMEA). This study provides insights into the popularity and prevalence of various fuzzy based risk assessment methods, guiding researchers, and practitioners in selecting appropriate methodologies for their studies or applications.
Keywords: Risk Assessment; Risk Analysis; Risk Management; Fuzzy Sets and Extensions; Risk Methodologies; EXTENSION; Computer Science; Mathematics